STUDI PENGEMBANGAN KAPASITAS LEMBAGA PENDIDIKAN PADA TINGKAT KELEMBAGAAN DI FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS DIPONEGORO - Arsa, Priska Lamella Cahya; Maesaroh, Maesaroh (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
Public demand for public services in the field of higher education is increasing, so that universities are competing improve its quality. One way in which the Faculty of Social and Political Science is the building of capacity in educational institutions at institutional level. The observation, document study and interviews with several informants indicate that the development of the capacity of educational institutions at institutional level in the Faculty of Social and Political Sciences when viewed from the existing dimensions, so it still needs to be improved to increase competitiveness in the global world.